Active use of solar radiation pressure for angular momentum control of the PROCYON micro-spacecraft. (November 2018) - Ito, T.; Ikari, S.; Funase, R.; Sakai, S.; Kawakatsu, Y.; Tomiki, A.; Inamori, T.
Abstract: This study proposes a solar sailing method for angular momentum control of the interplanetary micro-spacecraft PROCYON (PRoximate Object Close flYby with Optical Navigation). The method presents a simple and facile practical application of control during deep space missions. The developed method is designed to prevent angular momentum saturation in that it controls the direction of the angular momentum by using solar radiation pressure (SRP). The SRP distribution of the spacecraft is modeled as a flat and optically homogeneous plate at a shallow sun angle. The method is obtained by only selecting a single inertially fixed attitude with a bias-momentum state. The results of the numerical analysis indicate that PROCYON's angular momentum is effectively controlled in the desired directions, enabling the spacecraft to survive for at least one month without momentum-desaturation operations by the reaction control system and for two years with very limited fuel usage of less than 10 g. The flight data of PROCYON also indicate that the modeling error of PROCYON's SRP distribution is sufficiently small at a small sun angle (<10°) of the order of 10 − 9 Nm in terms of its standard deviation and enables the direction of the angular momentum around the target to be maintained. Highlights: The angular momentum control by solar sailing for deep space missions is proposed. The method is verified by simulation and experiment by the PROCYON micro-spacecraft. The simulated fuel usage of PROCYON is less than 10 g during the 2-year coasting. The flight data of PROCYON support the optical modeling assumptions of the method.